The causal relationship between the financial account and the current account: The case of Turkey - (:unkn) unknown (My University, 2011)
Financial account is known to serve to finance the current account imbalances. Yet, financial globalization seems to have changed this causality at least for some of the developing world countries.The aim of this paper is to analyze the interrelationship between the financial account, its components and the current account for Turkey. Results of the unit root tests reveal that the variables are naturally cointegrated as they are all integrated of order I (0). Granger causality analysisunder VAR framework disclosesthe existence of a unidirectional causality that runs from financial account to current account. The analysis also depicts that amongst the components of financial account there is aunidirectional causality that runs from fdi, equities and bank liabilities to current account. The results demonstrate that capital inflows cause current account deficitsand that the current account sustainability may be achievedvia better management of financial accountin Turkey.The short term bank liabilities should be further discouraged. Also, the financial market development should be further encouraged for the economy to increase its absorption capacity of massive financial account inflows. © EuroJournals Publishing, Inc. 2011.
Keywords: Current account adjustment; Granger causality; International investment; International lending; Long-term capital movements; Open economy macroeconomics; Short-term capital movements